Metal-Free Chemoselective ortho-C(sp2)–F Bond Hydroxylation and N-Trifluoroacylation of Fluoroarylamines for Domino Synthesis of 2-(N-Trifluoroacyl)aminophenols - Venkateswarlu, Vunnam; Balgotra, Shilpi; Aravinda Kumar, K. A.; Vishwakarma, Ram A.; Sawant, Sanghapal D. (Synlett, 2015)
A novel chemoselective reaction for the formation of C–O bonds by C(sp2)–F bond cleavage and concomitant N-trifluoroacylation of fluoroanilines using trifluoroacetic acid and Oxone® is presented. This domino reaction gives o-hydroxy-N-trifluoroacetanilides in good yields under metal-free conditions in a single step. Selective ortho-directed monohydroxylation and N-trifluoroacylation of 2- and 6-fluoro- or 2,6-difluoro-substituted anilines takes place in this transformation.
Keywords: C–F bonds; chemoselective reactions; C–O bonds; fluoroarylamine; hydroxylation